2015
DOI: 10.1242/jeb.123323
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction negatively affects multiple levels of the reproductive axis in male house finches, Haemorhous mexicanus

Abstract: Nutrition influences reproductive functions across vertebrates, but the effects of food availability on the functioning of the hypothalamicpituitary-gonadal (HPG) axis in wild birds and the mechanisms mediating these effects remain unclear. We investigated the influence of chronic food restriction on the HPG axis of photostimulated house finches, Haemorhous mexicanus. Food-restricted birds had underdeveloped testes with smaller seminiferous tubules than ad libitum-fed birds. Baseline plasma testosterone increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 95 publications
3
20
2
Order By: Relevance
“…9,52 We caution, however, that changes in the hypothalamic perikarya number, as measured in the present study, might not account for all the food-induced reproductive effects by themselves because food cues could affect also the release of hypothalamic neuropeptides in the median eminence, and the sensitivity of the anterior pituitary to GnRH/ GnIH, or of gonads to luteinising hormone. 9,12,26 Regardless of the possibility for more than one end point of the food-induced effects, the overall hypothalamic reproductive peptide levels in the current study correlated with earlier reported adverse effects of Figure 1. Values indicate the resuls of the two-way ANOVA (FA, food availability).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…9,52 We caution, however, that changes in the hypothalamic perikarya number, as measured in the present study, might not account for all the food-induced reproductive effects by themselves because food cues could affect also the release of hypothalamic neuropeptides in the median eminence, and the sensitivity of the anterior pituitary to GnRH/ GnIH, or of gonads to luteinising hormone. 9,12,26 Regardless of the possibility for more than one end point of the food-induced effects, the overall hypothalamic reproductive peptide levels in the current study correlated with earlier reported adverse effects of Figure 1. Values indicate the resuls of the two-way ANOVA (FA, food availability).…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, several bird studies have shown a negative impact of food deprivation on the hypothalamic‐pituitary‐gonadal (HPG) axis . For example, food availability affected circulating oestradiol levels in broiler hens and testosterone levels in male house finches ( Haemorhous mexicanus ) and Abert's towhees . Recently, Mishra and Kumar reported reduced oestradiol and mesotocin levels but not thyroxin and triiodothyronine levels in female zebra finches with access to food for 4 hours compared to food available ad lib., suggesting a negative effect of food restriction on the reproductive, not general, health, of breeding zebra finches …”
Section: Introductionmentioning
confidence: 99%
“…starvation) could have a direct effect by triggering a cascade of hypothalamic releases which negatively impact the activity of the hypothalamicpituitary-gonadal axis (Lynn et al, 2015;Davies et al, 2015;Rønning et al, 2009). This is evidenced by a food availabilityinduced alteration in the plasma levels of oestradiol in broiler hens (Onagbesan et al, 2006), testosterone in male house finches (Haemorhous mexicanus; Valle et al, 2015) and Abert's towhees (Davies et al, 2015) and thyroid hormones in Japanese quails, Coturnix c. japonica (Rønning et al, 2009). Consistent with this, food deprivation increased gonadotropin inhibiting hormone levels in zebra finches (Taeniopygia guttata; Lynn et al, 2015) and Pekin duck (Anas platyrhynchos domestica; Fraley et al, 2013).…”
Section: Introductionmentioning
confidence: 66%
“…Enzyme immunoassay kits from Enzo Life Sciences (Farmingdale, NY, USA) were used to measure plasma testosterone (ADI-901-065) and corticosterone (ADI-900-097). These assays have been validated for house finches (Deviche and Cortez, 2005;Valle et al, 2015).…”
Section: Hormone Assaysmentioning
confidence: 99%
“…For the testosterone assay, samples were run at a 1:15 dilution with 1% (of raw plasma volume) steroid displacement buffer (following Valle et al, 2015). Samples were run in duplicate, with samples assigned randomly across multiple plates except that all samples for a given individual were run on a single plate.…”
Section: Hormone Assaysmentioning
confidence: 99%